2018
DOI: 10.1155/2018/2859787
|View full text |Cite
|
Sign up to set email alerts
|

Pleurotus albidus Modulates Mitochondrial Metabolism Disrupted by Hyperglycaemia in EA.hy926 Endothelial Cells

Abstract: Hyperglycaemia exacerbates the production of reactive oxygen species (ROS), contributing to the multiple complications associated with diabetes. Mitochondrial dysfunction is also known to be associated with diabetes. Therefore, the aim of this work was to study the effect of Pleurotus albidus extract on the mitochondrial dysfunction induced by hyperglycaemia in EA.hy926 endothelial cells. The results showed that P. albidus treatment prevented the increase in the activity of complex I of the electron transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
1
5
0
2
Order By: Relevance
“…Resveratrol inhibits high glucose-induced mtROS production in human coronary artery endothelial cells via the intracellular target protein deacetylase silent information regulator (SIRT)2/SIRT1 [ 153 ]. In endothelial cells, SIRT1 overexpression attenuates mtROS production and overexpression of RSV and SIRT1 significantly reduces the level of H 2 O 2 and increased Mn-SOD and GSH expression in a concentration-dependent manner.…”
Section: High Glucosementioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol inhibits high glucose-induced mtROS production in human coronary artery endothelial cells via the intracellular target protein deacetylase silent information regulator (SIRT)2/SIRT1 [ 153 ]. In endothelial cells, SIRT1 overexpression attenuates mtROS production and overexpression of RSV and SIRT1 significantly reduces the level of H 2 O 2 and increased Mn-SOD and GSH expression in a concentration-dependent manner.…”
Section: High Glucosementioning
confidence: 99%
“…It inhibits the increase in electron transport chain complex I activity and decrease in ROS production induced by hyperglycaemia. It suppresses the oxidative damage of lipids and proteins, regulates imbalanced SOD and CAT activities, reduces the level of nitric oxide, restores mitochondrial function, and improves the vulnerability of endothelial cells to hyperglycaemia [ 153 ].…”
Section: High Glucosementioning
confidence: 99%
“…For the CIII, the treatment with JPE induced a significant increase in the activity, showing that the JPE can modulate the ETC activity. Corroborating our study, Gambato et al (2018) demonstrated an increase in CI activity in hyperglycemic endothelial cells, and the treatment with Pleurotus albidus extract, rich in phenolic compounds, was able to bring CI activity to the basal levels. Mustata et al (2005) also demonstrated that streptozotocin-induced diabetic rats showed a decrease in the specific activity of CIII in renal cortex and suggested that glycation may damage the CIII proteins.…”
Section: Discussionsupporting
confidence: 85%
“…[ 16,44 ] Mushrooms were recently discovered to be the primary source of ergothioneine which is known for its antioxidant properties. [ 45,46 ] Ergothioneine content of PSC was in range with the concentrations reported for other mushrooms, but lower than those reported for fruiting bodies of the Pleurotus species. [ 45 ] The chemical composition of mushrooms varies, according to the species, growth conditions and composition of the culture medium, which may be the reason for the variability of the chemical composition of PSC seen in this study.…”
Section: Discussionmentioning
confidence: 74%